Effect of Nitrogen on Properties of Na2O–CaO–SrO–ZnO–SiO2 Glasses. Issue 3 (30th November 2014) - Bachar, Ahmed; Mercier, Cyrille; Tricoteaux, Arnaud; Hornez, Jean‐Christophe; Leriche, Anne; Follet, Claudine; Revel, Bertrand; Hampshire, Stuart; Towler, Mark R.
Abstract : Glasses in the Na2 O–CaO–SrO–ZnO–SiO2 system have previously been investigated for suitability as a reagent in Al‐free glass polyalkenoate cements (GPCs). These materials have many properties that offer potential in orthopedics. However, their applicability has been limited, to date, because of their poor strength. This study was undertaken with the aim of increasing the mechanical properties of a series of these Zn‐based GPC glasses by doping with nitrogen to give overall compositions of: 10Na2 O–10CaO–20SrO–20ZnO–(40−3 x )SiO2 – x Si3 N4 ( x is the no. of moles of Si3 N4 ). The density, glass‐transition temperature, hardness, and elastic modulus of each glass were found to increase fairly linearly with nitrogen content. Indentation fracture resistance also increases with nitrogen content according to a power law relationship. These increases are consistent with the incorporation of N into the glass structure in threefold coordination with silicon resulting in extra cross‐linking of the glass network. This was confirmed using 29 Si MAS‐NMR which showed that an increasing number of Q 2 units and some Q 3 units with extra bridging anions are formed as nitrogen content increases at the expense of Q 1 units. A small proportion of Zn ions are found to be in tetrahedral coordination in the base oxide glass and the proportion of these increases with the presence of nitrogen.